1992
DOI: 10.1111/j.1747-6593.1992.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Plumbosolvency Effects and Control in Hard Waters

Abstract: A laboratory lead‐pipe rig has been used to support Anglian Water's successful orthophosphate dosing programme to reduce plumbosolvency. The hard waters in the region generally fall into low or high plumbosolvency categories according to the types of crystalline deposit formed. To improve the cost‐effectiveness of plumbosolvency control, the effects of temperature, phosphate doses, blending and alternation of these waters were investigated. Initial phosphate concentrations must be above 0.6 mg P/l (as phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 1 publication
6
34
0
Order By: Relevance
“…OrthoP treatment significantly reduced (64%) lead release from a mean of 72 AE 14 to 26 AE 9 mg/L ( Fig. 3b) within 8 days after the onset of treatment (mean: 24 AE 4 mg/L) consistent with observations by others (Xie and Giammar, 2011;Colling et al, 1992). The concentrations then remained relatively stable for 100 days (Fig.…”
Section: Release From 100%-pb Pipessupporting
confidence: 85%
“…OrthoP treatment significantly reduced (64%) lead release from a mean of 72 AE 14 to 26 AE 9 mg/L ( Fig. 3b) within 8 days after the onset of treatment (mean: 24 AE 4 mg/L) consistent with observations by others (Xie and Giammar, 2011;Colling et al, 1992). The concentrations then remained relatively stable for 100 days (Fig.…”
Section: Release From 100%-pb Pipessupporting
confidence: 85%
“…Laboratory plumbosolvency testing was undertaken by the standard method developed by Colling et al (1987Colling et al ( , 1992 for the major works requiring ortho-phosphate dosing and for a representative selection of the minor works requiring ortho-phosphate dosing. Testing involves pumping test water through sections of new lead piping at 258C with a water-pipe contact time of 30 minutes and measuring the lead emissions over a four week period.…”
Section: Ortho-phosphate Dose Selectionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] It is also accepted that the removal of natural organic matter (NOM) via coagulation and other water treatment steps can strongly influence lead release and metal corrosion through a variety of mechanisms. [10][11][12][13][14] One prior research article also attempted to quantify possible secondary benefits of aluminum from coagulation passing through water treatment (i.e., residual aluminum) in reducing lead release, but instead demonstrated that the aluminum tended to increase mobilization of lead. [1] It was speculated that the aluminum deposits sorbed lead from the plumbing material, causing excess lead to slough or dissolve into the water.…”
Section: Introductionmentioning
confidence: 97%